Skin changes after bariatric surgery - Ana Paula Dornelles da Silva Manzoni; Magda Blessmann Weber (Sociedade Brasileira de Dermatologia, 2015)
Today, obesity is considered an epidemic all over the world and it is recognized as one of the major public health problems. Bariatric surgery is considered an appropriate therapeutic option for obesity with progressively increasing demands. The changes resulting from massive weight loss after bariatric surgery are related to numerous complications. This article will present the dermatological alterations that can be found after bariatric surgery. They will be subdivided into dermatoses that are secondary to metabolic and nutritional disorders, those derived from cutaneous structural modifications after major weight loss and the influence the latter may have in improving of certain dermatoses.